Kondisi hematologi pemulung yang terpapar gas amoniak di tempat pembuangan akhir (TPA) sampah Batu Layang Pontianak - Ari Hepi Yanti, Niske Puspita Sari, Tri Rima Setyawati, (Jurnal Protobiont, 2014)
Ammonia is naturally formed from the breakdown of proteins in the decomposition of organic waste. The aim of this research is to understand the level of ammonia in ambient air and in the blood of the gerbage collectors at TPA Batu Layang Pontianak, as well as their hematologic condition after the gas exposed. This research had been done from October to November 2013. The ammonia level measurement was done by using Indofenol method of 0.0223 – 0.0817 ppm. Both male and female gerbage collectors, who had been working for more than 5 years, had the highest ammonia in blood levels of 0.719 mg/l and 0.705 mg/l respectively. The result of the regression analysis showed that the gerbage collectors, who had worked for longer period, had the higher ammonia and the lower hemoglobin level in their blood. The ammonia in blood level also caused the defective erythrocytes membrane and the systolic blood pressure, so that it became unstable. The result also showed that erythrocytes have shape abnormality which is categorised as elliptocytes. A garbage collector, who had the lowest ammonia level (0.058 mg/l) had the damaged erythrocytes percentage of 12.13%. Whereas, the garbage collectors that had the highest ammonia level (0.719 mg/l) had the damaged erythrocytes percentage of 30.09%.